The Effect of a Small Copper Addition on the Electrical Conductivity of Aluminum. Issue 6 (13th March 2020) - Lapovok, Rimma; Berner, Alex; Qi, Yuanshen; Xu, Chunjee; Rabkin, Eugen; Beygelzimer, Yan
Abstract : Aluminum powder blended with 10, 20, and 30 wt% of copper powder is compacted at 400 °C by four reciprocal extrusion passes. Simultaneous compaction and strengthening result in more than double increase in mechanical strength characteristics for 20 and 30 wt% of copper and a significant increase in electrical conductivity for 30 wt% of copper. This phenomenon is investigated here by the expansion of the "effective media" model for a random binary mixture so that it includes the presence of intermetallic phases and considers the distribution of large copper agglomerates. Abstract : Aluminum powder blended with 10–30 wt% of copper powder is compacted at 400 °C by reciprocal extrusion. Simultaneous compaction and strengthening result in significant increase in mechanical strength for 20 and 30 wt% of copper and in electrical conductivity for 30 wt% of copper. This phenomenon is investigated by the expansion of the "effective media" model.